Development of a quinoline-derived turn-on fluorescent probe for real time detection of hydrazine and its applications in environment and bioimaging. (October 2022) - Muthusamy, Selvaraj; Yin, Siqi; Rajalakshmi, Kanagaraj; Meng, Suci; Zhu, Dongwei; Xie, Meng; Xie, Jimin; Lodi, Rathna Silviya; Xu, Yuanguo
Abstract: Hydrazine is a highly toxic pollutant to the environment and living organisms. Therefore, it is an urgent need to detect hydrazine selectively, sensitively, and successfully in the real samples and biosystems. Thus, we designed a donor-π-acceptor fluorophore quinoline (Q ) appended 4-formylphenyl 2, 4-dinitrobenzoate (P-DNP ) to form a Schiff base QP-DNP for tracking hydrazine in real samples and biosystems. The probe observes an intramolecular charge transfer and aggregation induced emission sensing mechanisms on cleavage of ester bond upon nucleophilic substitution reaction with hydrazine and exhibited a "turn-on" fluorescence at green channel with the formation of quinoline-phenol. The proposed study was investigated through photophysical properties, 1 H NMR titration, HR-MS experiments, and density-functional theory calculations. The LOD of QP-DNP for hydrazine was calculated to be 55 nM and exhibited a high selectivity among possible competitive analytes. Additionally, the probe showed a remarkable emission colour changes on fabrication of paper sensor strips that can be discriminated in monitoring hydrazine vapor using smartphone and achieved an AND gate operation. Furthermore, QP-DNP was successfully applied to fluorescence imaging of hydrazine in live HeLa cells, monitoring of in situ hydrazine release as a metabolite of isoniazid drug administrated orally and determining hydrazine contamination in real samples. Graphical abstract: The nucleophilic substitution reaction of hydrazine with the probe was examined and the sensing mechanism was observed from ICT-ON to ICT-OFF with an elimination of 2, 4-dintrobenzoate. Image 1 Highlights: A novel quinoline appended chemosensor QP-DNP was developed for hydrazine detection. QP-DNP exhibits high sensitivity, selectivity towards hydrazine. "Turn-on" fluorescence approach is recorded with ICT and AIE sensing mechanisms. Hydrazine vapor is monitored on paper sensors using smartphone fluorescent imaging. The probe was employed for detecting endogenous hydrazine release as metabolite of isoniazid in mice.